Patient and economic benefits of psychological support for noncompliant patients - Reed, Phil; Osborne, Lisa A.; Whittall, C. Mair; Emery, Simon; Truzoli, Roberto (Frontiers in Psychology, 2022)
The current paper provides an overview of treatment noncompliance at various points in the treatment pathway, especially with respect to treatment for Pelvic-floor Dysfunction (PFD). The effects of noncompliance on healthcare are considered, and examples of supporting patients psychologically to increase compliance are discussed. An outline of a method to identify costs of non-compliance, and where such costs most intensely impact the healthcare system, is provided. It is suggested that psychological support is effective in terms of increased compliance and improved healthcare economics. The model is presented for PDF, but the principles developed can be generalised to many aspects of healthcare.